A universal pharmacy: Possible self‐medication using tree balsam by multiple Atlantic Forest mammals. (28th March 2022) - Kaisin, Olivier; Rocha, Fernanda Corrêa; Amaral, Rodrigo Gonçalves; Bufalo, Felipe; Sabino, Gabriel Pavan; Culot, Laurence
Abstract: We present camera trap evidence of 10 Atlantic Forest mammals fur‐rubbing, licking, or biting balsam from cabreúvas ( Myroxylon peruiferum, Fabaceae), native trees used in traditional medicine for their prophylactic and therapeutic virtues. Given the antiparasitic properties of cabreúvas, mammals may be using the balsam as topical self‐medication to repel ectoparasites. Abstract in Portuguese is available with online material. Abstract : We present camera trap evidence of 10 Atlantic Forest mammals fur‐rubbing, licking, or biting balsam from cabreúvas ( Myroxylon peruiferum, Fabaceae), native trees used in traditional medicine for their prophylactic and therapeutic virtues. Given the antiparasitic properties of cabreúvas, mammals may be using the balsam as topical self‐medication to repel ectoparasites. Resumo: Apresentamos evidências de armadilhas fotográficas de dez mamíferos da Mata Atlântica esfregando, lambendo ou mordendo bálsamo de cabreúvas ( Myroxylon peruiferum, Fabaceae), árvores nativas usadas na medicina tradicional por suas virtudes profiláticas e terapêuticas. Devidoàs propriedades antiparasitárias das cabreúvas, os mamíferos podem estar utilizando o bálsamo como automedicação tópica para repelir ectoparasitas.